2013
DOI: 10.3136/fstr.19.237
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Commercial Quality Evaluation of Yellowfin Tuna Thunnus albacares Meat Based on Myoglobin Properties

Abstract: Four quality grades (excellent, good, acceptable, and "not acceptable") of yellowfin tuna meat (Thunnus albacares), as judged by a professional appraiser, were compared based on the red/ox state and extractability of myoglobin (Mb). As a result, the metMb ratio of the "not acceptable" grade of meat was significantly higher than that of the other higher-grade samples. In contrast, the highest ratio of oxyMb was found in the "excellent" meat, followed by good > acceptable > "not acceptable" meats. Color measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
(57 reference statements)
0
7
0
3
Order By: Relevance
“…The molecular weight of the β component in the gelatin was estimated to be 226.65 kDa, and those of the α 1 and the α 2 components were 153.85 kDa and 134.54 kDa, respectively. Our previous study showed the yellowfin tuna skin gelatin extracted at 65 • C consisted of β component of 250 kDa, α1 of 129.67 kDa, and α 2 of 116.36 kDa [4]. Tuna gelatin has high molecular weight bands judging from abundant β components [13].…”
Section: Molecular Size and Hydrolysis Degreementioning
confidence: 99%
See 1 more Smart Citation
“…The molecular weight of the β component in the gelatin was estimated to be 226.65 kDa, and those of the α 1 and the α 2 components were 153.85 kDa and 134.54 kDa, respectively. Our previous study showed the yellowfin tuna skin gelatin extracted at 65 • C consisted of β component of 250 kDa, α1 of 129.67 kDa, and α 2 of 116.36 kDa [4]. Tuna gelatin has high molecular weight bands judging from abundant β components [13].…”
Section: Molecular Size and Hydrolysis Degreementioning
confidence: 99%
“…Frozen products are usually in the form of whole fish or loins. The freshness and quality of tuna meat is usually evaluated based on the oxidation extent of the muscle pigment, myoglobin [4]. The frozen tuna products could leave bones and skin wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Kesegaran ikan tuna biasanya diukur dari profil protein myoglobinnya. Nurilmala et al (2013) melaporkan karakterisasi myoglobin dapat dilakukan dalam penentuan kesegaran ikan tuna. Produk-produk tuna tersebut menghasilkan limbah berupa tulang dan kulit.…”
Section: Pendahuluanunclassified
“…The tuna group is easy to deteriorate by autooxidation (Nurilmala & Ochiai, 2016; (Nurilmala, Ushio, Watabe, & Ochiai, 2018) due to high myoglobin content (Nurilmala, Hedeki, Kaneko, & Ochiai, 2013). Based on the Import Refusal Report (IRR) system data, there were 246 tuna product rejections out of 1,457 Indonesian fishery product cases in 2018 at the American market.…”
Section: Introductionmentioning
confidence: 99%